(untitled) (Revista Educação, Artes e Inclusão, 2020)
The aim of this paper is to analyze how the University is positioned in front of the legal challenges for the implementation of the linguistic accessibility to deaf teachers, especially regarding the hiring of the professional interpreter as a means of inclusion of the teacher in the academic context. Thus, we seek to analyze the public policies aimed at the accessibility of this professional, since it is recurrent its insertion in the classrooms and, above all, in the universities. The purpose of this research is to discuss the promotion of linguistic accessibility to the deaf teacher at the UFG / RC. The theoretical basis of the study was based on the works of authors who work in the area of ​​inclusion and accessibility of deaf people such as Schubert (2012), Quadros (2004; 2005). We also conducted a documentary research on the measures taken to make the academic environment more accessible to these professionals in the institution. In addition, we analyze the legislation that covers matters concerning the accessibility that should be legally offered to deaf people as a support to correlate the information obtained. The research revealed that the University is not yet ready to include the deaf professional.